Genet and reef position effects in out-planting of nursery-grown Acropora cervicornis (Scleractinia:Acroporidae) in Montego Bay, Jamaica - Ross, Andrew M. (2014)
The reef-building coral Acropora cervicornis was a dominant ecosystem element on the Caribbean reef until the 1980s, when it declined by some 97% due primarily to anthropogenic ecosystem changes and disease. This branching species expanded its colony footprint and achieved local dominance largely through fragmentation and regrowth, thus is suited to nursery culture towards restoration. In this experiment, fragments of Acropora cervicornis of four lineages or genets were followed and measured for growth and health over 12 months in 2006 and 2007 on buoyant drop-loop line nurseries at one shallow and one deep fore-reef site in Montego Bay, Jamaica. Sixty-five of these corals were then out-planted to wild reef sites of similar depth and condition to their respective nurseries and monitored photographically for 11 months through 2007 and 2008. A period of rapid death was seen in the out-planted material at both sites over the first four months, followed by a period of relative stability or recuperation. Hermodice carunculata predation was the primary problem in the shallow fore-reef, and was combined with a banding syndrome at the deeper site. This syndrome was noted in the samples prior to planting, during a one week storage period on the seafloor. Continued slow decline occurred in the subsequent seven months in the shallow fore-reef site; however, regrowth was noted in the deeper site in the remaining material. Including these losses, final total live coral length was more than fourfold greater than the initial wild harvest: a net increase through multi-stage propagative restoration or coral gardening. Returns were noted particularly in the faster-growing genets of the nursery and larger planted corals tended to retain more material at eleven months, suggesting that propagative restoration programmes invest in stronger genets and larger corals. Adaptive management and maintenance gardening of the planted material and reef would likely have greatly improved outcomes. Rev. Biol. Trop. 62 (Suppl. 3): 95-106. Epub 2014 September 01.